Youth empowerment in health: a theoretical structure of literacy practices - Galvão, Dulce Maria Pereira Garcia (2023)
Barros, M. B. S. C., Nascimento, M. M. D. S., Rosário, H. R. V. D., Galvão, D. M. P. G., Silva, R. G. M. D., Soares, K. H. D., Leandro, V. C. C. A., & Monteiro, E. M. L. M. (2023). Youth empowerment in health: a theoretical structure of literacy practices. Revista gaucha de enfermagem, 44, e20220126. https://doi.org/10.1590/1983-1447.2023.20220126.en